Identification of Predictive Markers and Outcomes of Late-onset Pneumocystis jirovecii Pneumonia in Kidney Transplant Recipients. (23rd October 2020) - Kaminski, Hannah; Belliere, Julie; Burguet, Laure; Del Bello, Arnaud; Taton, Benjamin; Poirot-Mazères, Stéphane; Accoceberry, Isabelle; Delhaes, Laurence; Visentin, Jonathan; Gregori, Marco; Iriart, Xavier; Charpentier, Elena; et al.
Abstract: Background: In the era of prophylaxis, Pneumocystis pneumonia (PCP) has become a late-onset opportunistic infection requiring indications for prolonged prophylaxis to be defined. The primary objective of our study was therefore to evaluate risk factors associated with late-onset PCP. The secondary objective was to assess the impact of this infection on graft and patient survival. Methods: We conducted a French case-control study in Bordeaux and Toulouse center by matching 1 case to 1–2 controls from the same center based on the transplant date and the type of induction treatment. Results: Seventy cases and 134 controls were included. PCP occurred at a median of 3 years after transplantation. The total lymphocyte count and CD4 + and CD8 + T-lymphocyte values were lower in the cases than in their matched controls on the day of infection and annually up to 4 years earlier. The covariables independently associated with PCP were the total lymphocyte count 1 year before Pneumocystis, mTOR inhibitors used as maintenance immunosuppressive drugs, and the administration of corticosteroid boluses used in acute rejection. A total lymphocyte count threshold <1000/µL offered the best predictive value for infection occurrence. PCP was associated with high incidence of graft loss and patient death (30% and 17% respectively, 3 years after PCP). Conclusions: Pneumocystis pneumonia has dramatic consequences in kidney transplant recipients; a targeted prophylaxis based on simple criteria, such as chronic lymphopenia and/or history of corticosteroid boluses, could be useful to avoid life-threatening complications. Abstract : Total lymphocyte count <1000/µL at annual visit and corticosteroid boluses were the 2 parameters that were the most associated with an increased risk of Pneumocystis pneumonia and could be criteria for long-term prophylaxis.